2021
DOI: 10.1017/s1049096521001116
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Racial/Ethnic and Gender Gaps in Political Science PhD Students’ Methodological Self-Efficacy

Abstract: Most research on diversity within political methodology focuses on gender while overlooking racial and ethnic gaps. Our study investigates how race/ethnicity and gender relate to political science PhD students’ methodological self-efficacy, as well as their general academic self-efficacy. By analyzing a survey of 300 students from the top 50 US-based political science PhD programs, we find that race and ethnicity correlate with quantitative self-efficacy: students identifying as Black/African American and as M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Tormos-Aponte (2021) understands graduate school to be a “crucial battleground” for diversifying political science through admitting, retaining, and working to ensure the academic and professional success of underrepresented populations. URMs and women often experience isolation, discrimination, and limited access to information, sponsorship, mentorship, training opportunities, and professional recognition of their preferred research topics and methods (Almasri, Read, and Vandeweerdt 2022; Arnold, Crawford, and Khalifa 2016; Key and Sumner 2019; Kim and Grofman 2019; Means and Fields 2022; Mendez Garcia and Hancock Alfaro 2020; Monforti Lavariega and Michelson 2020; Shames and Wise 2017; Smith, Gillooly, and Hardt 2022; Teele and Thelen 2017).…”
Section: The Challengesmentioning
confidence: 99%
“…Tormos-Aponte (2021) understands graduate school to be a “crucial battleground” for diversifying political science through admitting, retaining, and working to ensure the academic and professional success of underrepresented populations. URMs and women often experience isolation, discrimination, and limited access to information, sponsorship, mentorship, training opportunities, and professional recognition of their preferred research topics and methods (Almasri, Read, and Vandeweerdt 2022; Arnold, Crawford, and Khalifa 2016; Key and Sumner 2019; Kim and Grofman 2019; Means and Fields 2022; Mendez Garcia and Hancock Alfaro 2020; Monforti Lavariega and Michelson 2020; Shames and Wise 2017; Smith, Gillooly, and Hardt 2022; Teele and Thelen 2017).…”
Section: The Challengesmentioning
confidence: 99%
“…However, other studies found no gender differences or even females having higher self-efficacy than males in certain fields. The studies which characterize the link between gender and science self-efficacy (Li and Singh, 2021 ; Bhati et al, 2022 ; Smith et al, 2022 ), have found that males reported possessing greater science self-efficacy than females (Anderman and Young, 1994 ; Lee et al, 2022 ). However, it seems to be discipline specific.…”
Section: Introductionmentioning
confidence: 99%
“…A range of issues in political science doctoral programs have recently been addressed in this journal, including students’ methodological self-efficacy (Smith, Gillooly, and Hardt 2022), mental health (Almasri, Read, and Vandeweerdt 2022), and the “hidden curriculum” (Barham and Wood 2022). However, at their core, all of the researchers question whether PhD programs are providing appropriate training and whether PhD students feel equipped for a future career.…”
mentioning
confidence: 99%